Alkali earth metal (Ca, Sr, Ba) based thermostable metal–organic frameworks (MOFs) for proton conduction - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Chemical communications (Cambridge, England), 2012)
Three new alkaline earth metal based MOFs have been synthesized by using 4,4'-sulfobisbenzoic acid (SBBA) and alkaline earth metal salts M(NO(3))(2), M = Ca, Sr, Ba. These MOFs exhibit interesting structural diversity, variable chemical stability as well as proton conductivity.